Impact of Billboards on Customer Purchase Intentions: A Study in KTM Commuter Stations, Malaysia - Krishnan, Mogana (2016)
Business is growing with the enhancement of technology globally. Marketers are also competing actively in the growing business to influence the purchasing behaviour of customers. Marketers are identifying the attractive design tools to deliver and communicate their ideas to customers and to advertise to attract and influence the targeted customers. Having said the existing technology to advertise such as newspapers, magazines, media and internet, yet do the customers still have time to look at this kind of ads in their busy schedule of work life (Latif & Abidin, 2011). By engaging their selves in many activities, customers do not have time to get information about the products in the markets. In this circumstance, marketers select the unique tool Billboard as the advertising tool to trap the customer’s intention to purchase (Balkafl, Akbulut and Kartopu, 2005) even though they are travelling. Many researchers identify that billboard has a unique characteristic which will trap the customers attention in the first look (Kelley and Jugenheimer 2004; Sissors and Baron 2002; Taylor 1997; Vanden Bergh and Katz 1999; Woodside 1990). In this research study, factors which have greater influences on the customer’s purchasing power decision through billboard advertisement are studies. A structured self-administered questionnaire is distributed to the respondent in random at KTM Komuter Station Seremban, Nilai and KL Central. The empirical result analysed proven how billboard influences the customer’s purchasing power towards the marketed product. The results indicated that awareness and desire has significant relationship between consumers’ desire towards billboards and purchase intention towards products advertised and awareness will lead to interest which eventually will also lead to desire. Therefore, in future marketers and advertising agencies need to be pro-active ensuring the suitability of the billboards design according to customer’s requirement and preference.